Hemoglobin (Hb)AI in Renal Failure: Formation of HbAI by Urea - KUROKAWA, Hidehiko; YAJIMA, Yoshitada; SAITO, Masayuki (Proceedings of the Symposium on Chemical Physiology and Pathology, 1982)
Effects of renal failure on HbAI levels were investigated. Criteria for glucose intolerance with normal HbAI levels were determined: normal OGTT or borderline OGTT with FBS below 117mg/dl, peak BS below 223mg/dl and ΣBS below 980mg/dl. By these criteria 30 patients with non-hemodialysed, non-diabetic CRF were selected and their HbAI levels were measured by ion-exchange column chromatography using Trivelli's method. HbAI levels elevated in patients with BUN levels above 50mg/dl and correlated significantly with BUN (r=0.83, p<0.0001) and CRTN (r=0.57, p<0.001). Red blood cells from normal subject were incubated for 5 days in 30mM triethanolamine HCl buffer, and HbAI levels were determined. In medium containing 500mg/dl of urea N (containing tracer dosis of 14C-urea) and 100mg/dl of glucose, HbAIa+b, HbAIc and the leading edge of HbAII increased markedly. HbAIa+b increased to 12.0% from 2.0%, and HbAIC to 19.2% from4.7%. 14C-urea was incorporated into HbAIa+b, HbAIc and the leading edge of HbAII. The ratios of D. P. M./ml to optical density of each eluate, which might imply numbers of urea molecule per hemoglobin, were greater in HbAIa+b and HbAIc than in the leading edge of HbAII. In media with urea N levels above 100mg/dl (100, 200, 300, 400 and 500) HbAI levels correlated highly with urea concentrations (r=0.99, p<0.0001). Addition of other uremic toxins (CRTN, UA, MG, GAA, GSA and GPA) to the incubation media did not significantly increase HbAI levels. These findings suggest that urea induces the elevation of HbAI levels due to the direct binding of urea to hemoglobin or due to the binding of cyanate, which is in equilibrium with urea in aqueous solution, and that HbAIa+b and HbAIc might bind more urea (or cyanate) molecules than the leading edge of HbAII. In diabetic CRF patients, therefore, an incraese in HbAI might be influenced not only by impaired glucose metabolism but also by high BUN levels.